Mitochondrial Protein Akap1 Deletion Exacerbates Endoplasmic Reticulum Stress in Mice Exposed to Hyperoxia - Sidramagowda Patil, Sahebgowda; Soundararajan, Ramani; Fukumoto, Jutaro; Breitzig, Mason; Hernández-Cuervo, Helena; Alleyn, Matthew; Lin, Muling; Narala, Venkata Ramireddy; Lockey, Richard; Kolliputi, Narasaiah; Galam, Lakshmi (Frontiers in Pharmacology, 2022)
Acute lung injury (ALI) and its severe manifestation, acute respiratory distress syndrome (ARDS), are treated with high concentrations of supplementary oxygen. However, prolonged exposure to high oxygen concentrations stimulates the production of reactive oxygen species (ROS), which damages the mitochondria and accumulates misfolded proteins in the endoplasmic reticulum (ER). The mitochondrial protein A-kinase anchoring protein 1 (Akap1) is critical for mitochondrial homeostasis. It is known that Akap1 deficiency results in heart damage, neuronal development impairment, and mitochondrial malfunction in preclinical studies. Our laboratory recently revealed that deleting Akap1 increases the severity of hyperoxia-induced ALI in mice. To assess the role of Akap1 deletion in ER stress in lung injury, wild-type and Akap1−/− mice were exposed to hyperoxia for 48 h. This study indicates that Akap1−/− mice exposed to hyperoxia undergo ER stress, which is associated with an increased expression of BiP, JNK phosphorylation, eIF2α phosphorylation, ER stress-induced cell death, and autophagy. This work demonstrates that deleting Akap1 results in increased ER stress in the lungs of mice and that hyperoxia exacerbates ER stress-related consequences.